2022
DOI: 10.1097/cad.0000000000001319
|View full text |Cite
|
Sign up to set email alerts
|

Selective poly adenylation predicts the efficacy of immunotherapy in patients with lung adenocarcinoma by multiple omics research

Abstract: The aim of this study was to find the application value of selective polyadenylation in immune cell infiltration, biological transcription function and risk assessment of survival and prognosis in lung adenocarcinoma (LUAD). The processed original mRNA expression data of LUAD were downloaded, and the expression profiles of 594 patient samples were collected. The (APA) events in TCGA-NA-SEQ data were evaluated by polyadenylation site use Index (PDUI) values, and the invasion of stromal cells and immune cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…The lncRNAs play an important regulatory role in the occurrence and development of diseases from cancer to cardiovascular diseases (21). Mounting studies (22)(23)(24)(25) have shown that lncRNAs can target miRNAs to play their function as Hub genes, that is, lncRNAs can affect the expression of proteincoding genes by competitively binding to miRNAs, thus reducing the degradation of protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNAs play an important regulatory role in the occurrence and development of diseases from cancer to cardiovascular diseases (21). Mounting studies (22)(23)(24)(25) have shown that lncRNAs can target miRNAs to play their function as Hub genes, that is, lncRNAs can affect the expression of proteincoding genes by competitively binding to miRNAs, thus reducing the degradation of protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated genes were mainly enriched in the processes of protein activation cascade, complement activation and so on. Zou et al 37 found that the mitotic regulation disorder during the cell cycle plays an important role in the process of colorectal cancer formation. Liu et al 38 investigated the tumor growth and anti-tumor therapy and reported that the activation of complement can promote the growth and proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…(2) We explored the KEGG and GO enrichment analysis and signaling pathways of DEGs gene and hub genes in the lung cancer prognostic model. (3) We built a more convincing prognostic model of lung cancer by combining the clinical trial data and gene transcription data. (4) The prognosis and 5-year survival rate of the patients with NSCLC were evaluated by independent prognostic analysis of its single factor and multiple factors, and the risk value of NSCLC patients was calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic surgery is widely used in clinical settings but the incidence of nausea and vomiting is high (8). It is higher than that of non-laparoscopic surgery, which is mainly related to patient factors, anesthesia factors, the type and duration of surgery, and carbon dioxide pneumoperitoneum (9). Various inducing factors, such as acetylcholine, norepinephrine, 5-HT, and other transmitters, stimulate peripheral receptors and the vomiting center.…”
Section: Introductionmentioning
confidence: 99%